Nonlinear relationship between serum 25-hydroxyvitamin D and lipid profile in Chinese adults - Wang, Qianqian; Miao, Xinlei; Hu, Manling; Xu, Fei; Tang, Guimin; He, Yangxuan; Song, Ziping; Zhao, Wan; Niu, Xiangjun; Leng, Song (Frontiers in Nutrition, 2024)
Background: Previous studies on the liner associations between serum 25-hydroxyvitamin D [25(OH)D] levels and lipid profiles revealed ambiguous findings. The current study therefore tried to elucidate the possible non-linear associations between 25(OH)D and lipid profiles. Methods: This study involved 8516 adult participants (aged 18-74 years, males N=3750, females N=4766) recruited from the Dalian health management cohort (DHMC). The risk (OR) for specific dyslipidemias was estimated across the serum 25(OH)D levels and the cut-off value for serum 25(OH)D were determined by using logistic regression, restricted cubic spline, and piecewise linear regression methods, adjusted for age, sex, season, and ultraviolet index. Results: In this study, a high prevalence of 25(OH)D deficiency was observed in the participants (65.05%). The level of 25(OH)D showed the inverse U-shaped correlations with the risks (ORs) of abnormal lipid profile, with inflection points observed at 23.7 ng/ml for hypercholesterolemia, 24.3 ng/ml for hypertriglyceridemia, 18.5 ng/ml for hyper-low-density lipoprotein cholesterolemia, 23.3 ng/ml for hypo-high-density lipoprotein cholesterolemia, 23.3 ng/ml for hyper-non-high-density lipoprotein cholesterol, and 24.3 ng/ml for high remnant cholesterol. The stratified analyses showed that the risk for most dyslipidemias related to deficiency of 25(OH)D was particularly increased among females aged 50-74 (except for hypertriglyceridemia, where the highest risk was among men aged 50-74 years), during winter/spring or under low/middle ultraviolet index environments. Conclusions: Nonlinear inverse U-shaped associations were observed between 25(OH)D levels and abnormal lipid profile. The risk was particularly increased among females aged 50-74, during winter/spring period or under lower ultraviolet index environments. In vitamin D deficient subjects (25(OH)D <20 ng/ml), a positive association of serum vitamin D levels with the risk for dyslipidemia was observed, which needs a further.